การคุ้มครองแรงงานข้ามชาติหญิงจากพม่า : กรณีศึกษาลูกจ้างทำงานบ้านในกรุงเทพมหานคร - ผจงรักษ์ ศรีไชยวงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of the study was to document the status of employment and working conditions of female migrant workers from Myanmar who work as domestic workers in Bangkok. This study also explores the extent of labor protections available to these female domestic workers. The study is based on data collected by using structured interviews with a sample of 120 female domestic workers from Myanmar working in Bangkok. The questionnaire was designed based on the conceptual framework of the research and from in-depth interviews with 10 key informants including government officials, and staff of NGOs working with female migrant domestic workers from Myanmar. This study covers general information about the decision of migrants to seek work in Thailand. In terms legal protection, most migrants do not have a written employment agreement, but have been informed of the employment terms verbally. Many migrant domestic workers have a variety of tasks to perform. In the course of extending legal protections to workers. Domestic workers receive additional benefits, such as days off and paid leave. The law protects against child labor as per Ministerial Act 14 (2012) under the Labor Protection Law of 1998. Thai labor law does not extend protection regarding payment of minimum wage and work hours for domestic workers. However based on the data collected, it appears that most of the migrant workers in this category receive wages that meet the legal minimum wage requirements. Their work day may span 15 to 17 hours, but this includes periods of rest during the day. As for social protection, there is no labor union for domestic workers in Thailand. But there are non-formal group support processes, including weekly literacy classes conducted by NGOs on Sundays. The Thai government ensures the minimum standard of social protection and welfare regarding accommodation, sanitary food and water, and health insurance which provides access to subsidized clinical care as needed. Most of the foreign domestic workers in Thailand have health insurance cards and can access basic education in the non-formal education program, as well as special courses provided by NGOs. Nevertheless, They work in private residences, Which makes it difficult to inspect the working conditions and identify labor rights violations. Thus, protecting the rights of foreign domestic workers largely depends on the adherence to the law and regulations by the employer. Therefore, it is recommended that the Thai government should have a mechanism to allow inspectors to enter the homes where foreign domestic workers work to ensure that work conditions comply with the law. The government should support various media to increase awareness of the legal labor rights of workers, including domestic workers. The employers of these workers and their migrant employees should be informed about the legal protections and benefits in relevant language.